2006
DOI: 10.1063/1.2209179
|View full text |Cite
|
Sign up to set email alerts
|

Recording potential of bit-patterned media

Abstract: A comprehensive analysis of the areal density potential of bit-patterned media recording shows that the recording performance is dominated by written-in errors. The statistical fluctuations of the magnetic properties and the locations of the individual bits lead to error probabilities so that some dots are either not recorded at all or cannot be recorded in the time window necessary to ensure synchronized writing. The highest areal densities are obtained with a combination of a pole head, a soft magnetic under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
101
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 13 publications
0
101
0
Order By: Relevance
“…Due to the necessary miniaturization of such devices and the proximity of the superparamagnetic limit, 8 the magnetic interaction between the neighboring cells 9 is becoming a more and more important parameter that has to be understood and, hitherto, controlled. Also, it has recently been shown that the dilution of a small amount of magnetic transition metal atoms in a semiconductor matrix can lead to the self organization of well ordered, transition metal rich, magnetic nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the necessary miniaturization of such devices and the proximity of the superparamagnetic limit, 8 the magnetic interaction between the neighboring cells 9 is becoming a more and more important parameter that has to be understood and, hitherto, controlled. Also, it has recently been shown that the dilution of a small amount of magnetic transition metal atoms in a semiconductor matrix can lead to the self organization of well ordered, transition metal rich, magnetic nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Another key issue is the stringent requirement on switching field distribution (SFD) for ultrahigh density HAMR media (<5%), 10,12 where any residual A1 phase could be detrimental. Therefore, a complete understanding of the low anisotropy A1 to high anisotropy L1 0 phase transformation is critical.…”
mentioning
confidence: 99%
“…Bit patterned magnetic recording media (BPMR), where each bit is defined by one dot in the patterned dot arrays, is considered to be a promising ultra high density recording technology for the future. [1][2][3][4] In bit patterned media, in order to maximize the signal-to-noise ratio, 5 a continuous magnetic film with perpendicular magnetic anisotropy is patterned into an ordered array to record the data. [6][7][8][9] Another effective way to further increase the signal-to-noise ratio is to increase the aspect ratio (the ratio between the height and the diameter) of each dot.…”
Section: Perpendicular Coercivity Enhancement Of Copt/tin Films By Nimentioning
confidence: 99%